Post-operative radiochemotherapy in patients with gastric cancer: one department’s experience of 56 patients - Spych, M (The British Institute of Radiology., 2011)
OBJECTIVES: Prognosis in patients with locally advanced stomach cancer undergoing surgery alone is poor. High local failure rates in gastric cancer have been reported of up to 70%. When a relapse occurs, attempts at curative treatment are generally unsuccessful. A retrospective analysis was performed in order to determine whether post-operative radiochemotherapy improves treatment results in patients with locally advanced gastric cancer. METHODS: Between November 2004 and July 2008, 56 patients with clinical Stage IB–IV cancer of the stomach underwent curative gastrectomy and adjuvant radiochemotherapy. Patients with distant metastases were excluded from the analysis. The total radiation dose was 45.0 Gy. The chemotherapy regimen comprised a 5 day cycle of 5-fluorouracil at 425 mg m(–2) and leucovorin at 20 mg m(–2). Overall survival and disease-free survival, as well as toxicity, were estimated for all patients. RESULTS: Within the study group there were 7 (13%) local recurrences, 4 (7%) distant metastases and 8 (14%) local and distant relapses. The 2 year overall survival was 48%. A total of 19 (34%) patients developed Grade 3 gastrointestinal toxicity. There were no treatment-related deaths. CONCLUSION: Post-operative radiochemotherapy is an effective and safe regimen in patients with curatively resected locally advanced gastric cancer.